Optimizing ceftriaxone prophylaxis in elective laparoscopic cholecystectomy: single-dose versus multiple-dose antibiotics - Kumar Mishra, Rohit; N Shah, Jay; Shrestha, Alok; Kumar Yadav, Basant; Adhikari, Ganesh (Journal of Chitwan Medical College, 2025)
Introduction: Prophylactic antibiotics are widely used to reduce the risk of wound infection. However, the necessity of postoperative antibiotic use, its dose and duration remain controversial. This study aimed to compare a single dose of antibiotic against multi doses on wound infection rate in elective laparoscopic cholecystectomy. Method: A prospective comparative study was conducted at department of surgery in Chitwan Medical College from Sep to Dec 2024. Ethical approval was obtained. Symptomatic cholelithiasis patients undergoing elective laparoscopic cholecystectomy were allocated for single dose (SD) or multiple dosage (MD) groups. First case was selected by lottery and then alternated. Injection 1 gram of ceftriaxone was administered to the SD group at the time of anaesthesia induction, while the MD group got it twice daily for two days. Data on clinico-demographics and wound infection status were recorded in a structured proforma. Frequency, percentage, measure of central tendency and measure of dispersion were calculated. Chi square test/Fischer’s exact was used in IBM SPSS for association between SD/MD and wound infection rate. A p≤0.05 was considered statistically significant. Result: The study included 126 patients, SD=59 and MD=67. The mean age was 46.68±15.43 years (range: 19–81 years). Wound infections occurred in two patients in each group (SD=3.4%, MD=3.0%), the difference was statistically not significant (p=0.897). Conclusion: Wound infection following laparoscopic cholecystectomy was low around 3%, and there was no significant difference in the single dose antibiotics versus multiple doses.